2020
DOI: 10.1016/j.chom.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Depletion of Bacteria from Mixed Populations by Programmable Adhesion with Antagonistic Competitor Cells

Abstract: Selective and targeted removal of individual species or strains of bacteria from complex communities can be desirable over traditional, broadly acting antibacterials in several contexts. However, generalizable strategies that accomplish this with high specificity have been slow to emerge. Here we develop programmed inhibitor cells (PICs) that direct the potent antibacterial activity of the type VI secretion system (T6SS) against specified target cells. The PICs express surface-displayed nanobodies that mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 61 publications
(69 reference statements)
0
58
0
Order By: Relevance
“…P. aeruginosa possesses 3 genes for T6SS, H1-, H2-, and H3-T6SS, and H2- and H3-T6SS act not only against prokaryotes but also against eukaryotes (Hood et al, 2010 ; Trunk et al, 2018 ). A recently published study showed that programmed inhibitor cells can target bacterial species in a complex microbial community using T6SS (Ting et al, 2020 ), indicating a potential role for T6SS in altering microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa possesses 3 genes for T6SS, H1-, H2-, and H3-T6SS, and H2- and H3-T6SS act not only against prokaryotes but also against eukaryotes (Hood et al, 2010 ; Trunk et al, 2018 ). A recently published study showed that programmed inhibitor cells can target bacterial species in a complex microbial community using T6SS (Ting et al, 2020 ), indicating a potential role for T6SS in altering microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to be considered is engineering microbes for therapy in the form of synthetic probiotics, which can lead to the controlled release of these microbial strains providing localised therapeutics under specific conditions. There are many examples in the literature of probiotic strains that have been engineered to act as drug delivery vectors at the site of infection [ 72 , 83 ]. However, there are still multiple challenges in the clinical application of engineered probiotics, such as stable long-term colonization of the niche [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent reports have shown that antibiotic treatment or selective enrichment of certain microbial species in the gut can indeed limit the effectiveness of immune check point therapy in cutaneous melanoma [ 97 , 98 ]. Interestingly, a recent study demonstrated targeted depletion of bacteria from a mixed population by programmed inhibitor cells that can direct the antibacterial activity against specified target cells using the type VI secretion system (T6SS) [ 99 ]. Such an approach where topical treatment selectively enriches skin commensals or targets specified microbes (pathogenic), known to be involved in immune responses [ 100 ], could also be envisioned for modulating UVR-induced immune suppression and the efficacy of phototherapy ( Figure 1 ).…”
Section: Perspectivesmentioning
confidence: 99%